A model of integration ISO 9001 with Lean six sigma and main benefits achieved - Sá, José Carlos (2020)
The main purpose of this article is to depict the integration of Lean tools with requirements of ISO 9001:2015 standard as an operationalisation and support tool for a Quality Management System (QMS). The research was carried out through a questionnaire, which was sent to 2040 Portuguese companies. From the two hundred responses, 77 of them were validated (companies certified by at least one quality management system and which simultaneously have lean six sigma (LSS) tools and/ or techniques implemented) corresponding to the sample of this study. Additionally, the research was also based on a case study in a footwear company where the model was applied. This research proposes a model for integrating Lean tools and requirements of ISO 9001:2015. This integration allows the QMS to become more practical and dynamic, reinforcing the creation of value for the organisation. As main benefits, we can highlight, among others: improvement of problem solving, waste reduction, improvement in internal communication, and increase in productivity. This article aims at becoming a relevant contribution to business management as it displays the main tools and methodologies to implement and sustain a QMS.